2015
DOI: 10.14260/jemds/2015/887
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Practice (Kap) of Blood Donation Among MBBS Students of a Medical College in Kollam, Kerala

Abstract: BACKGROUND:Blood transfusion is a very crucial component to manage patients suffering from various medical conditions. Voluntary blood donors are the need of the hour. There is a need to spread awareness among general population and students about blood donation to maintain a regular blood supply. Young medical students can serve as best example to take a lead in this noble cause. OBJECTIVE: To assess the Knowledge, Attitude and Practice (KAP) of Blood Donation among 1 st and 2 nd year MBBS students of a Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 8 publications
3
28
3
Order By: Relevance
“…11,13,18 Further the study by Chopra D et al and Ahmad Nadeem Aslani et al also emphasized that 49.8% and 45% of the medical professionals had correct knowledge about the interval between two blood donations respectively. 7,8 But our study reported higher proportion of interns having the correct knowledge about the interval.…”
contrasting
confidence: 48%
See 2 more Smart Citations
“…11,13,18 Further the study by Chopra D et al and Ahmad Nadeem Aslani et al also emphasized that 49.8% and 45% of the medical professionals had correct knowledge about the interval between two blood donations respectively. 7,8 But our study reported higher proportion of interns having the correct knowledge about the interval.…”
contrasting
confidence: 48%
“…Various studies have been conducted in general population and health professionals, but very few studies are conducted on young doctors. [6][7][8][9][10][11][12][13][14][15][16][17][18] So, this study was conducted to determine the knowledge and attitude about donor eligibility, safety and prevailing practices pertaining to voluntary blood donation among interns.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Aslami AN et al thus showing that religion hardly plays any role in donors decision to donate blood. 12 Foremost reasons in the present study for not donating blood were occurrence of anaemia followed by objections from family. Meinia SK et al reported fear of needle, anemia occurrence after blood donation and objection from family members as the reasons for not donating blood among the respondents.…”
Section: Discussionmentioning
confidence: 71%
“…90.6% of the respondents knew about the suitable age for blood donation which was almost in line with the rates reported by Chopra et al (90%) and Aslami AN et al (85%). 11,12 Almost 93% of the respondents knew about the interval between two blood donations. A slightly lower rate to the tune of 80% and 76% in this regard were reported by Agravat Amit et al and Meinia SK et al respectively.…”
Section: Discussionmentioning
confidence: 99%